Peningkatan Profitabilitas Pada Industri Perbankan Go-Publik di Indonesia - Adi Santoso (Esensi: Jurnal Bisnis dan Manajemen, 2016)
The Profitability Improvement at Go-Public Islamic Banks in IndonesiaThe aim at the study to examine and analyze the impact growth of profitability through its capital adequacy ratio, operating expense to operating income, loan to deposit ratio and  non perfoming loan in the banking industry go public in indonesia. The results show that operating expense to operating income and loan to deposit ratio have significantly effect to return on asset while the capital adequacy ratio,and non perfoming loan not significantly effect to return on asset. Capital adequacy ratio, operating expense to operating income, loan to deposit ratio and non perfoming loan not significantly effect to return on equity. While for variable stock returns are significantly influenced only by the capital adequacy ratio, operating expense to operating income, loan to deposit ratio, return on asset and  return on equity while non perfoming loan not significantly effect to stock returnsDOI: 10.15408/ess.v6i1.3117